Youth entrepreneurship in agriculture and rural development: Nigeria - Babu, Suresh Chandra; Zhou, Yuan (International Food Policy Research Institute, 2020)
Young people engaging in agricultural entrepreneurship in developing countries face several challenges. Above all, they lack adequate access to important resources and opportunities. These include land, credit, farm inputs, agronomic and vocational training, insurance, and lucrative markets. Addressing these challenges requires answers to some key questions: Which factors drive the success of youth entrepreneurs in developing countries? What type of business ‘ecosystem’ is best suited for their development? What roles should the various stakeholders play in making youth entrepreneurship flourish nationally? How can young people expand their start-ups to become small, medium, or largescale businesses? To answer these questions, the International Food Policy and Research Institute (IFPRI) and the Syngenta Foundation for Sustainable Agriculture (SFSA) developed a conceptual framework. This framework classifies contextual and driving factors that contribute to the success of youth entrepreneurship. There are four broad categories for intervention: policy, institutional, technological, and individual capabilities.